2013
DOI: 10.2111/rem-d-12-00157.1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Precipitation Affect Steer Weight Gains Differentially by Stocking Rate in Northern Mixed-Grass Prairie

Abstract: Cattle weight gain responses to seasonal weather variability are difficult to predict for rangelands because few long-term (.20 yr) studies have been conducted. However, an increased understanding of temperature and precipitation influences on cattle weight gains is needed to optimize stocking rates and reduce enterprise risk associated with climatic variability. Yearling steer weight gain data collected at the USDA-ARS High Plains Grasslands Research Station at light, moderate, and heavy stocking rates for 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 33 publications
1
26
1
Order By: Relevance
“…Additionally, livestock weight gains were more sensitive to seasonal weather influences as SR increased (Reeves et al, 2013b(Reeves et al, , 2014. These results can be used by land managers to adjust SR levels to seasonal weather variability.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Additionally, livestock weight gains were more sensitive to seasonal weather influences as SR increased (Reeves et al, 2013b(Reeves et al, , 2014. These results can be used by land managers to adjust SR levels to seasonal weather variability.…”
Section: Introductionmentioning
confidence: 84%
“…The CV values for PSC (0.29-0.37), Maint (0.21-0.20) and TotTDN (0.18-0.28) changed less with SR compared to the CV change of SWG. This result indicated that the quadratic response of TotTDN and linear response of Maint to SR resulted in high yearly variability of SWG at high SR levels, which explained the higher sensitivity of SWG to seasonal weather variations under higher SR levels (Reeves et al, 2013b(Reeves et al, , 2014. Fig.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…The Treatments evaluated in the study included two permanent vegetation pastures and one seeded forage pasture, each of which belong to a network of long-term grazing studies investigating grazing management effects on animal performance and plant species composition and production (Reeves et al 2013). The permanent pastures included a moderately grazed pasture (MGP) and heavily grazed pasture (HGP), both established in 1916 on native rangeland and managed without the application of tillage, fertilizer, herbicides, or fire and Kentucky bluegrass (30% of the species composition) while the remainder of the species were similar to MGP.…”
Section: Site and Treatment Descriptionmentioning
confidence: 99%